Breaking news how the Associated Press has covered war, peace, and everything else (Princeton Architectural Press, 2007)
The reporter who filed the last dispatch before falling with Custer at his "last stand" against the Sioux.The Honolulu bureau chief who looked up from his breakfast table to see Japanese planes flying low andcalled San Francisco, managing to dictate a single paragraph before all communications to the mainlandwere cut. The Saigon bureau chief who served Coca-Cola and pound cake to three North Vietnamesesoldiers before writing the bulletin announcing the fall of Saigon. These are but a few of the gripping anddramatic stories reported first by the Associated Press in the past century and a half.In How the Associated Press Has Covered War, Peace, and Everything Else, the Associated Press throws open its archives and invites readers into its news bureaus and out into the field to witness first hand its groundbreaking reporting on presidents, elections, wars, civil rights, trials and crimes, disasters, business, and major sports events.